Terrorism and the regional and religious risk perception of foreigners: The case of German tourists - Gabriel M. Ahlfeldt; Bastian Franke; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2009)
This paper analyses how German tourists react to unanticipated shocks that alter their risk perception of selected tourism destinations. Using a difference-in-difference strategy which flexibly accounts for macroeconomic conditions and also addresses potential problems of serial correlation, we isolate significant effects of the 9/11 (2001) terrorist attacks, as well as for the attacks in Egypt (1997), Tunisia (2002), Morocco (2003) and Indonesia (2003). These terror attacks impacted especially on Islamic countries all over the world, indicating a transmission mechanism driven by ethnic and religious proximity. At the same time, tourism into Islamic countries was temporarily substituted by tourism to (south) European countries.
Keywords: R19; D89; 330; Terrorism; 9/11; Islamic Countries; Tourism Demand